2005
DOI: 10.1177/1077558704273806
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Private and Public Health Insurance on Medication Use for Adults with Chronic Diseases

Abstract: This article examines the impact of public and private health insurance on the use of medications for California adults with any of four chronic diseases: heart disease, high blood pressure, diabetes, and asthma. The data set used is the 2001 California Health Interview Survey. Multivariate analyses were conducted on individuals who had been diagnosed with each of these diseases. Controlling for various demographic, health status, and employment characteristics, the authors find that the uninsured are far less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 3 publications
3
24
0
Order By: Relevance
“…We found that those covered by private plans were significantly more likely to be undiagnosed when they actually had diabetes than were those covered by government insurance. This finding may seem counterintuitive, but we know that some private insurance companies provide limited coverage for preventive care (17,23), and private coverage tends to be more discontinuous (24). It is worth noting that some government health plans (e.g., those offered through the Department of Veterans Affairs) provide relatively effective preventive care for their enrollees with diabetes (17), and the Veteran's Affairs professional staff may accordingly be more attuned to recommendations for diabetes screening.…”
Section: Multivariate Analysismentioning
confidence: 67%
“…We found that those covered by private plans were significantly more likely to be undiagnosed when they actually had diabetes than were those covered by government insurance. This finding may seem counterintuitive, but we know that some private insurance companies provide limited coverage for preventive care (17,23), and private coverage tends to be more discontinuous (24). It is worth noting that some government health plans (e.g., those offered through the Department of Veterans Affairs) provide relatively effective preventive care for their enrollees with diabetes (17), and the Veteran's Affairs professional staff may accordingly be more attuned to recommendations for diabetes screening.…”
Section: Multivariate Analysismentioning
confidence: 67%
“…[1][2][3] An analysis of the Health and Retirement Study (HRS), a longitudinal survey of noninstitutionalized adults in the United States, reported that lack of health insurance was associated with higher mortality in white adults. 4 In an analysis of the Third National Health and Nutrition Examination Survey (NHANES III), investigators found that blood pressure was 59% more likely to be controlled in hypertensive participants with private health insurance than in those without health insurance.…”
Section: Index Wordsmentioning
confidence: 99%
“…17 Other studies show that in comparison to people with heart diseases and stroke who have insurance, the uninsured with heart diseases and stroke experience higher mortality rates, 18 -20 poorer blood pressure control, 21 greater neurologic impairments and longer lengths of hospital stay after stroke, 18 as well as a lower likelihood of taking appropriate medications. 22 In today's complex healthcare environment, even individuals with health insurance can find it difficult to access medically necessary healthcare services due to rising insurance premiums, significant deductible and copayment requirements, insurance restrictions (such as limitations in access to rehabilitative services, exclusions for preexisting conditions and caps on lifetime benefits) and other insurance practices that favor low-risk enrollees over individuals with or at risk for developing chronic disease. In addition, the fragmented nature of the healthcare delivery system and the lack of coordination of healthcare services often create challenges for all patients with chronic illness, including those with cardiovascular diseases and stroke.…”
Section: Lack Of Health Insurancementioning
confidence: 99%